2020
DOI: 10.1097/md.0000000000021191
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of regorafenib after sorafenib monotherapy with advanced hepatocellular carcinoma including Child–Pugh classification B

Abstract: The therapeutic effect of regorafenib was previously demonstrated in patients with advanced hepatocellular carcinoma (HCC) and Child–Pugh classification A (CP-A) whose disease progressed during sorafenib treatment in a phase III trial. However, treatment options are limited for patients with advanced HCC other than CP-A. In this study, we aimed to evaluate the therapeutic effect of regorafenib on advanced HCC patients including those with Child–Pugh classification B (CP-B). We retrospectively analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A search of the PubMed database identified 24 cohorts in 23 studies encompassing 2074 patients treated with REG (Figure 1 and Table ) 11,14–35 . Similarly, six cohorts from six studies comprising 621 patients treated with RAM 12,36–40 were identified, as well as seven cohorts from six studies involving 1240 patients treated with CAB 13,23,33,41–43 (Figure 1 and Tables and , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…A search of the PubMed database identified 24 cohorts in 23 studies encompassing 2074 patients treated with REG (Figure 1 and Table ) 11,14–35 . Similarly, six cohorts from six studies comprising 621 patients treated with RAM 12,36–40 were identified, as well as seven cohorts from six studies involving 1240 patients treated with CAB 13,23,33,41–43 (Figure 1 and Tables and , respectively).…”
Section: Resultsmentioning
confidence: 99%